Spatial-temporal pattern of mosquito-borne disease occurrence based on epidemiological data: a case study from Terengganu - Nik Abdull Halim, Nik Muhammad Hanif; Che Dom, Nazri; Dapari, Rahmat (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The trend of several mosquito-borne diseases in Malaysia has shown an increasing pattern over the past few years despite close monitoring and continuous control initiatives by public health authority. The objective of this study is to determine the spatial and temporal epidemiology of mosquito-borne disease in Terengganu from the year 2009 to 2018. Terengganu has been selected because it is geographically unique and experiences two monsoon seasons per year. Methods: Weekly surveillance data of mosquito-borne diseases which include dengue fever, malaria, filariasis, Japanese Encephalitis (JE) and chikungunya from 2009 to 2018 were collected from the Terengganu State Health Department. The variables included in the dataset mainly comprises of disease onset, diagnosis, case category, area (district) and site of onset. The data has been monitored spatial and temporal in which to explore the distribution pattern of the disease. The annual average for each type of mosquito-borne disease was determined using time-series and is further analysed by using geographical information system (GIS) tools to form spatial statistical analysis. Results: Results indicate that the temporal distribution of the mosquito-borne disease in Terengganu increases slightly despite a fluctuating pattern from the year 2009 to 2018 and there are between each type of mosquito-borne disease. Spatial analysis showed different stratification between seasons as well as the areas that are more susceptible to each disease. Conclusion: The results obtained in this present study through spatial and temporal analysis revealed that mosquito-borne diseases show a dynamic pattern in distribution. It can be concluded that the occurrence of the diseases depends on the geographical area and the weather within the region. This study provides public health authorities with a comprehensive assessment that will be useful for surveillance and monitoring, as well as for predicting and managing mosquito-borne disease outbreaks effectively.